Efficient removal of cadmium using facile functionalized of mesoporous silica via a biomimetic coating. Issue 22 (15th February 2016) - Chen, Yan; Gao, Junkai; Wen, Xiaofei; Wu, Wenfeng
Abstract : A mesoporous material (DMOS), prepared by grafting polydopamine onto meso-structured silica (MOS), was developed as a sorbent to sequestrate Cd 2+ . Abstract : A mesoporous material (DMOS), prepared by a facile surface modification strategy based on grafting polydopamine onto meso-structured silica (MOS), was developed as a sorbent to sequester Cd 2+ . The method used to modify MOS was simple, facile and cost-effective. The DMOS was characterized by SEM, TEM, XRD, BET and FT-IR, showing that the material had clear multilayer structures, a large surface area of 431 m 2 g −1 and a large pore size of 12.7 nm. The influences of pH, contact time, solid-to-liquid ratio, ionic strength and adsorption–desorption cycles on the sorption process were investigated. It was demonstrated that the adsorption capacity of Cd 2+ by DMOS was dramatically improved by functionalization, with the maximum adsorption capacity of 107 mg g −1 at pH 6.0, and that the sorption equilibrium time was 90 minutes. Additionally, the influence of the solid-to-liquid ratio and ionic strength on the sorption was very weak, and the Cd 2+ adsorption capacity of regenerated DMOS still remained 86.5% after ten adsorption–desorption cycles. All the results illustrated that the DMOS exhibited excellent performance for the removal of Cd 2+ .